Accurate simulation of the herniated cervical intervertebral disc using controllable expansion: a finite element study. Issue 8 (11th June 2021) - Liang, Dong; Tu, Guan-Jun; Han, Ya-Xin; Guo, Da-Wei
Abstract: Expansions were carried out in finite element (FE) models of disc hernia including symmetric (median, lateral, paramedian) and asymmetric types. In all models, lubricous disk bulging that applied a linear compression to the anterior part of the cord was observed at the posterior surfaces of the expansion zone, respectively. The shape and position of protrusions varyed with the temperature, magnitude, and location of expanding elements. The geometric deformation and stress distribution of the spinal cord increased as the extent of compression grew. This method is in possession of enormous potential in promoting further individualized research of cervical spondylotic myelopathy.